1999
DOI: 10.1103/physrevb.59.14712
|View full text |Cite
|
Sign up to set email alerts
|

Glassy nature of stripe ordering inLa1.6xNd0.4Sr

Abstract: We present the results of neutron-scattering studies on various aspects of crystalline and magnetic structure in single crystals of La1.6−xNd0.4SrxCuO4 with x = 0.12 and 0.15. In particular, we have reexamined the degree of stripe order in an x = 0.12 sample. Measurements of the width for an elastic magnetic peak show that it saturates at a finite value below 30 K, corresponding to a spin-spin correlation length of 200Å. A model calculation indicates that the differing widths of magnetic and (previously report… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
119
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(138 citation statements)
references
References 56 publications
19
119
0
Order By: Relevance
“…Finally, we note that the low-energy magnetic excitations in the normal state of La 2−x Sr x CuO 4 look very much like those observed 48,49 in stripe-ordered La 1.48 Nd 0.4 Sr 0.12 CuO 4 . In the latter system, one interprets the incommensurate excitations as spin waves of the magnetically ordered system.…”
Section: Resultsmentioning
confidence: 79%
“…Finally, we note that the low-energy magnetic excitations in the normal state of La 2−x Sr x CuO 4 look very much like those observed 48,49 in stripe-ordered La 1.48 Nd 0.4 Sr 0.12 CuO 4 . In the latter system, one interprets the incommensurate excitations as spin waves of the magnetically ordered system.…”
Section: Resultsmentioning
confidence: 79%
“…Glassiness is, however, also present in materials where stripe order is well-defined and relatively long range [8]. Furthermore, from the T dependence of an average 139 La spin-lattice relaxation rate T −1 1 , Curro et al [12] concluded that the distribution of magnetic correlation times (Color online) Sketch of the phase diagram of La2−xSrxCuO4.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the temperature of magnetic freezing, T g , in La 2−x Sr x CuO 4 is peaked in the vicinity of x 1 8 ( Fig. 1), and neutron scattering studies [5,6,7] reveal long-range antiferromagnetic order with the same typical modulation as in the materials presenting direct evidence for charge stripe order [8]. Another approach relies on electronic and magnetic inhomogeneities generated by quenched disorder [9].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence for stripe correlations has been provided by neutron studies in Nd-doped La 1.875 Sr 0.125 CuO 4 and in other cuprates and nickelates. 1,2 The spatial organization of the stripe structures is a subject of much debate. [3][4][5][6][7][8] Stripe formation is characterized by the temperatures of charge (T charge ) and spin T spin ordering with T charge ϾT spin .…”
mentioning
confidence: 99%